Phase-object analysis with a speckle interferometer - Angel, Luciano (2002)
We describe the characteristics of a double-exposure specklegram obtained through a double-aperture system, by introduction of a wedge in front of one aperture in one exposure. It is assumed that a uniform displacement of the diffuser is produced between exposures. The average intensity distribution and visibility of the interferometric fringes in the Fourier plane are analyzed. An alternative interferometric technique for phase-object detection is proposed.